Association of Oral Anticoagulation With Stroke in Atrial Fibrillation or Heart Failure: A Comparative Meta-Analysis. Issue 10 (20th July 2021) - Reddin, Catriona; Judge, Conor; Loughlin, Elaine; Murphy, Robert; Costello, Maria; Alvarez, Alberto; Ferguson, John; Smyth, Andrew; Canavan, Michelle; O'Donnell, Martin J.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Atrial fibrillation and heart failure with reduced ejection fraction (HFrEF) are common sources of cardioembolism. While oral anticoagulation is strongly recommended for atrial fibrillation, there are marked variations in guideline recommendations for HFrEF due to uncertainty about net clinical benefit. This systematic review and meta-analysis evaluates the comparative association of oral anticoagulation with stroke and other cardiovascular risk in populations with atrial fibrillation or HFrEF in sinus rhythm and identify factors mediating different estimates of net clinical benefit. Methods: PubMed and Embase were searched from database inception to November 20, 2019 for randomized clinical trials comparing oral anticoagulation to control. A random-effects meta-analysis was used to estimate a pooled treatment-effect overall and within atrial fibrillation and HFrEF trials. Differences in treatment effect were assessed by estimating I 2 among all trials and testing the between-trial-population P -interaction. The primary outcome measure was all stroke. Secondary outcome measures were ischemic stroke, hemorrhagic stroke, mortality, myocardial infarction, and major hemorrhage. Results: Twenty-one trials were eligible for inclusion, 15 (n=19 332) in atrial fibrillation (mean follow-up: 23.1 months), and 6 (n=9866) in HFrEF (mean follow-up: 23.9 months). There were differences in primary outcomes between trial populations, with all-cause mortality included for 95.2% of HFrEF trial population versus 0.38% for atrial fibrillation. Mortality was higher in controls groups of HFrEF populations (19.0% versus 9.6%) but rates of stroke lower (3.1% versus 7.0%) compared with atrial fibrillation. The association of oral anticoagulation with all stroke was consistent for atrial fibrillation (odds ratio, 0.51 [95% CI, 0.42–0.63]) and HFrEF (odds ratio, 0.61 [95% CI, 0.47–0.79]; I 2 =12.4%; P interaction=0.31). There were no statistically significant differences in the association of oral anticoagulation with cardiovascular events, mortality or bleeding between populations. Conclusions: The relative association of oral anticoagulation with stroke risk, and other cardiovascular outcomes, is similar for patients with atrial fibrillation and HFrEF. Differences in the primary outcomes employed by trials in HFrEF, compared with atrial fibrillation, may have contributed to differing conclusions of the relative efficacy of oral anticoagulation.